Molecular basis for cytokine biomarkers of complex 3D microtissue physiology in vitro - Asthana, Amish; Kisaalita, William S. (Drug discovery today, 2016)
Physiologically more-relevant’claims are readily made for cells cultured on any surface or in a scaffold that provides loosely defined 3D geometry. A set of tools to measure culture ‘3D-ness’ more accurately are needed. Such tools should find applications in fields ranging from high-throughput identification of substrates for tissue engineering and regenerative medicine to cell-based screening of drug candidates. Until now, these fields have not provided a consensus for the most promising place to initiate the search. Here, we review recent advances in transcriptomic, proteomic, inflammation and oncology-related pathways, as well as functional studies that strongly point to cytokines as the most likely compounds to form the missing consensus.